THE EFFECT OF PROBLEM-BASED LEARNING ON STUDENTS’ CRITICAL THINKING SKILLS IN IPAS LEARNING ON CURRENCY VALUE TOPIC - Dwi Safitri; Priyono Tri Febrianto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study was conducted in response to the low critical thinking skills of fourth-grade students in Integrated Science and Social Studies (IPAS), which were reflected in low learning engagement and achievement scores below the minimum mastery criteria. The study aimed to examine the effect of the Problem-Based Learning (PBL) model on students’ critical thinking skills in the topic of buying and selling activities at SDN Patereman 1. A quantitative approach with a pre-experimental method using a one-group pretest–posttest design was employed. The participants consisted of 29 fourth-grade students selected through saturated sampling. Data were gathered through observation and test instruments, and analyzed using normality testing, paired sample t-test, and N-Gain analysis. The findings reveal that students’ critical thinking skills improved, as shown by the increase in the mean score from 48.45 in the pretest to 72.24 in the posttest. The hypothesis testing resulted in a significance value below 0.05, indicating a statistically significant difference after the implementation of the treatment. Furthermore, the N-Gain score of 0.5764 falls within the moderate category, showing a reasonable level of improvement. Overall, the results indicate that the Problem-Based Learning model has a significant effect on improving students’ critical thinking skills and can be effectively applied in elementary-level IPAS learning.